Thanks for the memories - Ahern, Cecelia (Harper, 2009)
Joyce Conway, recovering from an accident that caused her to miscarry and proved to be the last straw for her already failing marriage, is puzzled to find herself with knowledge and memories not her own, and repeated encounters with a strange man for whom she feels an unusual attraction convinces her something strange is happening.